Bone mineral density in primarily preadolescent children with hemoglobin E/β-thalassemia with different severities and transfusion requirements - Nakavachara P. (2023)
Background: Children with β-thalassemia major and β-thalassemia intermedia frequently have low bone mass. However, studies of bone mineral density (BMD) in children with transfusion-dependent (TD) or non-transfusion-dependent (NTD) hemoglobin (Hb) E/β-thalassemia are scarce. Objectives: To determine the prevalence of low bone mass among mostly preadolescent children with NTD and TD Hb E/β thalassemia and the related factors. Methods: We investigated the BMD of the lumbar spine (LSBMD) and total body (TBBMD), measured by dual-energy X-ray absorptiometry, of 59 children with NTD Hb E/β-thalassemia and 50 with TD Hb E/β-thalassemia. Results: The median age of the patients was 10.4 (6.2–13.5) years in the NTD group and 10.3 (5.9–14.1) years in the TD group. These children had a relatively low prevalence of low bone mass (NTD: 1.7%–10.2%; TD: 4%–14%). The values varied with the bone site measured and the BMD size-adjustment method used (height age vs. bone age). The NTD group had significantly lower TBBMD Z-scores (adjusted for height age) than the TD group. The proportion of patients with low lumbar spine bone mass (adjusted for bone age) was significantly higher for the TD group than for the NTD group. Conclusions: Our study demonstrates that most children with either disease had normal BMD. Patients with the NTD form had a lower TBBMD than those with the TD form. Low bone mass affected the lumbar spine of patients with TD Hb E/β-thalassemia more than those with the NTD form.